Analysis of healthy cohorts for single nucleotide polymorphisms in C1q gene cluster - MARIA A. RADANOVA; PETYA P. IVANOVA; DIANA G. IVANOVA (Journal of BioScience and Biotechnology, 2015)
C1q is the first component of the classical pathway of complement activation. The coding region for C1q is localized on chromosome 1p34.1–36.3. Mutations or single nucleotide polymorphisms (SNPs) in C1q gene cluster can cause developing of Systemic lupus erythematosus (SLE) because of C1q deficiency or other unknown reason. We selected five SNPs located in 7.121 kbp region on chromosome 1, which were previously associated with SLE and/or low C1q level, but not causing C1q deficiency and analyzed them in terms of allele frequencies and genotype distribution in comparison with Hispanic, Asian, African and other Caucasian cohorts. These SNPs were: rs587585, rs292001, rs172378, rs294179 and rs631090. One hundred eighty five healthy Bulgarian volunteers were genotyped for the selected five C1q SNPs by quantative real-time PCR methods. International HapMap Project has been used for information about genotype distribution and allele frequencies of the five SNPs in, Hispanics, Asians, Africans and others Caucasian cohorts. Bulgarian healthy volunteers and another pooled Caucasian cohort had similar frequencies of genotypes and alleles of rs587585, rs292001, rs294179 and rs631090 SNPs. Nevertheless, genotype AA of rs172378 was significantly overrepresented in Bulgarians when compared to other healthy Caucasians from USA and UK (60% vs 31%). Genotype distribution of rs172378 in Bulgarians was similar to Greek-Cyriot Caucasians. For all Caucasians the major allele of rs172378 was A. This is the first study analyzing the allele frequencies and genotype distribution of C1q gene cluster SNPs in Bulgarian healthy population.